A ciphertext‐policy hidden vector encryption scheme supporting multiuser keyword search. Issue 6 (23rd June 2014) - Zhenhua, Liao; Jinmiao, Wang; Bo, Lang
Abstract In cloud computing, large amount of data can be effectively stored and managed. People could outsource the encrypted data using searchable encryption (SE) for data security and efficient retrieval. However, most existing SE schemes only support the single‐user access, and multiuser searchable encryption is required in many enterprise applications. From the attribute‐based encryption (ABE), we found that the flexibility and usability of encryption schemes can be greatly improved by embedding attribute‐based access policy in the ciphertext. In this paper, by using the idea of ABE, we propose a ciphertext‐policy hidden vector encryption (CPHVE) scheme to support both encryption and search operations for multiple users. In the scheme, a keyword is encrypted with an attribute‐based access policy, which can be searched when the users' attributes satisfy the policy. The security of CPHVE is also defined and proved in this paper. Moreover, the CPHVE scheme is based on standard complexity assumptions on bilinear groups of prime order, thus it is more efficient than the existing schemes. Copyright © 2014 John Wiley & Sons, Ltd.